2013
DOI: 10.1021/nn401856u
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Pharyngeal and Intestinal pH of Caenorhabditis elegans and Real-Time Luminal pH Oscillations Using Extended Dynamic Range pH-Sensitive Nanosensors

Abstract: Extended dynamic range pH-sensitive ratiometric nanosensors, capable of accurately mapping the full physiological pH range, have been developed and used to characterize the pH of the pharyngeal and intestinal lumen of Caenorhabditis elegans in real-time. Nanosensors, 40 nm in diameter, were prepared by conjugating pH-sensitive fluorophores, carboxyfluorescein (FAM) and Oregon Green (OG) in a 1:1 ratio, and a reference fluorophore, 5-(and-6)-carboxytetramethylrhodamine (TAMRA) to an inert polyacrylamide matrix.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 49 publications
6
86
0
Order By: Relevance
“…Therefore, we tested tetR-VMA2 virulence in a C. elegans model of infection (34). C. elegans is an ideal organism for the study of virulence in C. albicans vma mutants, as the pH of the larynx and intestine of C. elegans nematodes, where C. albicans infection occurs (34,35), ranges from 3.5 to 5.5 (57). For these studies, we analyzed infection at the permissive pH and temperature, under acidic pH conditions (pH 4.0) and at 30°C, because tetR-VMA2 is unable to grow at neutral pH and low temperatures (i.e., 25°C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested tetR-VMA2 virulence in a C. elegans model of infection (34). C. elegans is an ideal organism for the study of virulence in C. albicans vma mutants, as the pH of the larynx and intestine of C. elegans nematodes, where C. albicans infection occurs (34,35), ranges from 3.5 to 5.5 (57). For these studies, we analyzed infection at the permissive pH and temperature, under acidic pH conditions (pH 4.0) and at 30°C, because tetR-VMA2 is unable to grow at neutral pH and low temperatures (i.e., 25°C).…”
Section: Resultsmentioning
confidence: 99%
“…The infection culminates in C. albicans hyphae piercing the C. elegans cuticle and killing the worm (35). Because the C. elegans gastrointestinal tract and pharynx have very low pH, ranging from pH 5.5 in the pharynx to pH 3.5 in the lower intestine (57), C. elegans is an ideal model to study V-ATPasemediated pathogenesis in vivo. We tested the contribution of VMA2 to C. albicans virulence in an acidic environment, i.e., under pH conditions permissible for growth of V-ATPase-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…3.5 in the posterior part. [45] In vitro experiments showed that the combination of acidic pH and ionic strength of the citrate buffer pH 4.6 promoted the aggregation and precipitation of the AuNPs ( Figure S5). Therefore, these conditions may compromise AuNP stability in the most posterior part of the alimentary system.…”
Section: Np Status Inside C Elegansmentioning
confidence: 99%
“…58,59 In another study, the presence of digestive enzymes and acidic environment of the digestive system of C. elegans were found to dissolve metal nanoparticles and thus have toxic effects on C. elegans. 60,61 However, in the case of CNMA-GNPs, the silica coating must be digested before the gold core is accessible to the intestinal environment, which suggests that the silica coating on CNMA-GNPs protects the bare GNPs and thus decreases potential toxicity issues.…”
mentioning
confidence: 99%